Pembelajaran Bahasa Arab dalam Kurikulum Dayah Jeumala Amal Pidie Jaya : (Tinjauan Kritis) - Mishbahul Munir (JURNAL AL-IHDA : Media Ilmiah Bahasa Arab, 2022)
This article specifically reviewed Arabic learning in the Dayah Jeumala Amal Curriculum. The review based on the Arabic Language Curriculum Model and Principle as stated by Moh. Taufiqurrahman and Muhammad Ikrom Karyodiputro in Islamic Academika published in 2019. Researchers see this concept is quite significant to see various sharp and measurable reviews of language learning, especially Arabic. Furthermore, the curriculum is reviewed by looking at the philosophical foundation, psychological foundation, sociological foundation, organizational foundation and linguistic foundation. Furthermore, this study sees the relevance, efficiency, effectiveness and worthiness of Arabic learning in this curriculum. Researchers use qualitative methods to understand various phenomena that occur in the field related to the object of study and study related documents. The research was conducted in Dayah Jeumala Amal by involving related figures and teachers, especially the curriculum drafting team and Arabic Language Teachers Institution to obtain objective data.